Flow-Diversion Panacea or Poison? - Zanaty, Mario; Chalouhi, Nohra; Tjoumakaris, Stavropoula I.; Rosenwasser, Robert H.; Gonzalez, L. Fernando; Jabbour, Pascal (Frontiers in Neurology, 2014)
Endovascular therapy is now the treatment of choice for intracranial aneurysms (IAs) for its efficacy and safety profile. The use of flow diversion (FD) has recently expanded to cover many types of IAs in various locations. Some institutions even attempt FD as first line treatment for unruptured IAs. The most widely used devices are the pipeline embolization device (PED), the SILK flow diverter (SFD), the flow redirection endoluminal device (FRED), and Surpass. Many questions were raised regarding the long-term complications, the optimal regimen of dual antiplatelet therapy, and the durability of treatment effect. We reviewed the literature to address these questions as well as other concerns on FD when treating IAs.